Evaluasi pelaksanaan authentic assessment berdasarkan kurikulum 2013 dalam pembelajaran ekonomi di Sma Islam Al-Hidayah Jember - Arie Eko Cahyono (Universitas PGRI Madiun, 2017)
This study aims to determine (1) the implementation of authentic assessment is based on the curriculum in 2013 at SMA Islam Al-Hidayah Jember; and (2) the obstacles in the implementation of authentic assessment in SMA Islam Al-Hidayah Jember. This study is an evaluation research with quantitative descriptive approach. This was an evaluation study employing the quantitative descriptive design. The research subjects were economics teachers. The data were collected through observations, documentation, and interviews. They were analyzed by means of the descriptive method. The results of the study are as follows. (1) Authentic assessment in economics learning at SMA Islam Al-Hidayah Jember, is fairly well implemented; 77% has been implemented in accordance with the indicators and23% has not been implemented in accordance with the indicators. The indicators that have not been implemented in the planning aspect is the assessment design in the syllabus; in the implementation aspect it includes information of the assessment system; and in the processing aspect it includes the follow-up of the results of the analysis of the learning achievement assessment.; (2) The constraints in the authentic assessment implementation include: (a) complex planning, (b) the number of components that the teachers have to take into account at the same time in the assessment implementation, and (c) the attitude assessment that has to pay attention to a large number of students in detail.